Pengaruh Produk Domestik Regional Bruto (PDRB) Terhadap Penerimaan Pajak Daerah Kabupaten Gresik Tahun 2012-2024 - Dina Puspita Sari (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research target explaining the effect of Gross Regional Domestic Product (GRDP) on local tax revenue in Gresik Regency. Local tax revenue is one of the main sources of Regional Original Revenue which is used to finance various public needs and facilities that cannot be provided by the private sector. As stated by Mahmudi (2010), local revenue including local tax revenue can be seen from the value of Gross Regional Domestic Product (GRDP). GRDP is the market value of all products and services produced in a region during a certain period. This research uses a quantitative approach with an associative research type. The data used is secondary data from the documentation study of the Regional Budget and Revenue realization report and the realization of GRDP in the Gresik Regency Central Statistics Agency report for the 2012-2024 period. The analysis method uses simple linear regression, classical assumption test, t-test, and 𝑅 2 test using SPSS version 27 software. The t-test results show that the GRDP variable has a positive and significant effect on local tax revenue in Gresik Regency with a sig value. < 0.001 < 0.05 and the regression coefficient of the GRDP variable which is positive, namely 0,013. The R square value in the 𝑅 2 test of 0.965 indicates that 96.5% of the variation in local tax revenue in Gresik Regency can be explained by GRDP. The dominant contribution of the processing industry sector in the GRDP structure of Gresik Regency is the main factor in the magnitude of the influence of GRDP on local tax revenue in Gresik Regency.
Reaploud Repository February_Hasyim
Keywords: Gross regional Domestic Product (GRDP); local tax revenues; local own revenue